Recent Developments in Discontinuous Galerkin Finite Element Methods for Partial Differential Equations: 2012 John H Barrett Memorial Lectures - Feng, Xiaobing (Springer International Publishing Imprint: Springer, 2014)
A quick tutorial on discontinuous Galerkin methods for elliptic problems -- Discontinuous Galerkin methods for time dependent problems: survey and recent developments -- Adaptivity and error estimation for discontinuous Galerkin methods.- $C^0$ interior penalty methods for 4th order problems.- Devising superconvergent discontinuous Galerkin methods.- A local time stepping Runge-Kutta discontinuous Galerkin method for hurricane storm surge modeling.- An overview of the discontinuous Petrov-Galerkin method.- Discontinuous Galerkin methods for radiative transport equations.- Error control for discontinuous Galerkin methods for first order hyperbolic problems.- Virtual elements and discontinuous Galerkin methods.- Time-discrete higher order ALE formulations: a DG approach -- Discontinuous finite element methods for coupled surface-subsurface flow and transport problems
Keywords: Konferenzschrift; Diskontinuierliche Galerkin-Methode; Partielle Differentialgleichung